2021
DOI: 10.3390/nu13103578
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Copper/Zn Ratio in a Series of Children with Chronic Diseases: A Cross-Sectional Study

Abstract: Copper is an essential micronutrient for humans. A cross-sectional and comparative study was done to assess serum Cu levels and serum copper/zinc (Cu/Zn) ratio and its association with nutritional indicators in a series of children and adolescents with chronic diseases. Anthropometric, biochemical, dietary, body composition, and bone densitometry assessments were carried out. Serum Cu and Zn were measured by atomic absorption spectrophotometry. Seventy-eight patients (55% women) participated. The mean serum Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 108 publications
1
33
0
Order By: Relevance
“…Serum prealbumin ≤ 18 mg/dL, albumin ≤ 3.5 g/dL as visceral protein reserve, transferrin ≤ 200 mg/dL, lymphocytes < 2000 cell/mm 3 , total cholesterol (TC) > 200 (mild-moderate risk) and >225 mg/dL (high risk), and low-density-lipoprotein cholesterol (LDL-C) > 115 (mildmoderate risk) and >135 mg/dL (high risk) were used as cutoffs to evaluate abnormal values. Serum levels of folic acid; beta-carotene; vitamins B12, C, D, E, calcium, phosphorus, iron, zinc [40], and copper [41]; total immunoglobulin (Ig) G, IgG1-4, IgA, IgM, and IgE; C3 and C4 complement; CD3, CD4, CD8, CD16+56, CD19 lymphocytes, and CD4/CD8 ratio; and insulin-like growth factor-1 (IGF-1) and insulin-like growth factor-binding protein 3 (IGFBP3) were assessed.…”
Section: Laboratory Explorationmentioning
confidence: 99%
“…Serum prealbumin ≤ 18 mg/dL, albumin ≤ 3.5 g/dL as visceral protein reserve, transferrin ≤ 200 mg/dL, lymphocytes < 2000 cell/mm 3 , total cholesterol (TC) > 200 (mild-moderate risk) and >225 mg/dL (high risk), and low-density-lipoprotein cholesterol (LDL-C) > 115 (mildmoderate risk) and >135 mg/dL (high risk) were used as cutoffs to evaluate abnormal values. Serum levels of folic acid; beta-carotene; vitamins B12, C, D, E, calcium, phosphorus, iron, zinc [40], and copper [41]; total immunoglobulin (Ig) G, IgG1-4, IgA, IgM, and IgE; C3 and C4 complement; CD3, CD4, CD8, CD16+56, CD19 lymphocytes, and CD4/CD8 ratio; and insulin-like growth factor-1 (IGF-1) and insulin-like growth factor-binding protein 3 (IGFBP3) were assessed.…”
Section: Laboratory Explorationmentioning
confidence: 99%
“…19 As regards the mechanisms of the link between altered Cu/Zn status and BC, high circulating Cu and Cu/Zn ratio, and low Zn, have been associated with chronic inflammation in various human studies. [20][21][22][23][24][25] There is considerable evidence that chronic inflammation in associated with increased risk of several cancers including BC. [26][27][28] A previous study on our ORDET cohort found that high levels of the inflammatory marker C reactive protein were associated with increased risk of postmenopausal BC.…”
Section: Discussionmentioning
confidence: 99%
“…The design of this cross-sectional and comparative study ( Figure 1 ) was previously published in children and adolescents with chronic diseases [ 41 , 42 ]. We performed this study in the Nutrition Unit of the Pediatrics Service at the University Clinical Hospital in Valladolid, Spain.…”
Section: Methodsmentioning
confidence: 99%